The new open research plattforms: A potential game-changer? - De-Castro, Pablo (Anuario ThinkEPI, 2018)
With the recent launch of a number of F1000-based open research platforms, research funders like Wellcome Trust, Bill and Melinda Gates Foundation, and the Irish Health Research Board are stepping up their attempt to shift the scholarly publishing landscape into a more suitable environment for the implementation of their open science policies. Weeks ago, the European Commission released the call for bids for its Open Research Europe, thus joining this potentially game-changing move towards open peerreview, article-level metrics, pre-prints, and tighter control of publishing by Academia. This text examines the various objectives of these platforms and argues that this well-aimed move may not succeed if it fails to persuade researchers of the value of such publishing outlets. There is a clear role for institutions, whose open science advocacy strategies towards their authors can be adjusted to include the dissemination and promotion of such platforms.